(untitled) (Bangladesh Critical Care Journal, 2022)
Gastroduodenal intussusception caused by a gastric polypoid mass is a very rare cause of gastric outlet obstruction.We report a rare case of a 65 year old lady who presented with a 6 months history of postprandial abdominal discomfort with recurrent vomiting and a 5 kg of weight loss during the last 5 months period. After several investigations a tubulovillous adenoma with a long pedicle arising from the gastric wall of upper body was found to be prolapsing into the duodenum through the pylorus producing gastroduodenal intussusception and thus giving rise to features of gastric outlet obstruction. Although gastroduodenal intussusception caused by a gastric polypoid mass is a very rare cause of gastric outlet obstruction, it should be kept in mind as one of the differentials. Bangladesh Crit Care J March 2022; 10 (1): 68-70